Sosialisasi literasi keuangan bagi generasi muda di kalangan mahasiswa Universitas Muhammadiyah Klaten - Putri, Arie Rachma; Husna, Faizah Khotimatul; Ismail, Habib; Indraswati, Tutik; Sulistya, Safira Nur (Nur Science Institute, 2024)
Financial literacy is crucial for helping individuals manage money effectively. The target of this activity is all students from the Faculty of Social Sciences and Humanities at Universitas Muhammadiyah Klaten. This event aims to provide students with knowledge and insights on financial literacy and prevent them from falling into scams and online loan traps. Additionally, students will better understand saving, investing, and utilizing financial technology (fintech). The methods used in this activity include delivering material, discussions, and evaluations through questionnaires distributed after the event. It is hoped that participants will become more prudent in managing their finances and avoiding harmful practices through this activity. The outcome of this event is that participants have a better understanding of financial literacy, with the expectation that the knowledge gained can be applied in their daily lives. With strong financial literacy, individuals can better navigate economic changes, optimize financial opportunities, and achieve their goals more effectively.